2003
DOI: 10.1191/0960327103ht335oa
|View full text |Cite
|
Sign up to set email alerts
|

Combined efficacies of lipoic acid and meso-2,3-dimercaptosuccinic acid on lead-induced erythrocyte membrane lipid peroxidation and antioxidant status in rats

Abstract: One of the most intriguing phenomenon observed during lead toxicity has been attributed to lead-induced oxidative stress. The combined effect of DL-a-lipoic acid (LA) and meso 2,3-dimercaptosuccinic acid (DMSA) on lead-induced alterations in selected parameters, which are indicators of oxidative stress in erythrocytes, have been studied. Lead acetate (Pb, 0.2%) was administered in drinking water for 5 weeks to induce toxicity. LA (25 mg/ kg body weight per day i.p.) and DMSA (20 mg/kg body weight per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 59 publications
7
40
0
1
Order By: Relevance
“…The GSH levels of control group was 1.05 μg of GSH/mg protein, and in 1 week lead exposed group was 0.95 μg of GSH/mg protein, and in 3 weeks lead exposed group was 0.88 μg of GSH/mg protein. Several studies reported that lead toxicity decreases GSH levels (Bechara 2004;Patra et al 2001;Sivaprasad et al 2003). In 3 weeks lead plus ginger treated group the GSH level was increased (0.94 μg of GSH/mg protein).…”
Section: Methodsmentioning
confidence: 93%
“…The GSH levels of control group was 1.05 μg of GSH/mg protein, and in 1 week lead exposed group was 0.95 μg of GSH/mg protein, and in 3 weeks lead exposed group was 0.88 μg of GSH/mg protein. Several studies reported that lead toxicity decreases GSH levels (Bechara 2004;Patra et al 2001;Sivaprasad et al 2003). In 3 weeks lead plus ginger treated group the GSH level was increased (0.94 μg of GSH/mg protein).…”
Section: Methodsmentioning
confidence: 93%
“…In this study, it was observed that a dose-dependent decrease in the Fe-NTA mediated oxidative stress in kidney of T. divaricate pretreated rats, which is manifested by a decrease in the susceptibility of microsomal membrane for LPO as well as H 2 O 2 generation. Studies with a number of models show that the metabolism of xenobiotics often produced GSH depletion, which increases the sensitivity of organ to oxidative and chemical injury (Sivaprasad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental research has indicated that after exposure to lead there is an increased amount of oxidized glutathione (GSSG) with a parallel drop of reduced glutathione (GSH) in different organs (Gurer et al, 1999;Sivaprasad et al, 2003). Similarly, incubation of human blood in the presence of lead compounds causes a drop of GSH concentration (Hunaiti and Soud, 2000).…”
Section: Introductionmentioning
confidence: 99%